Internal mammary perforators as recipient vessels for deep inferior epigastric perforator and muscle-sparing free transverse rectus abdominis musculocutaneous flap breast reconstruction in an Asian population - Halim, Ahmad Sukari; Ahmad Alwi, Akmal Azim (Lippincott Williams & Wilkins, 2014)

(untitled)
Background: The use of internal mammary perforators (IMP) as recipient vessels in autologous free flap breast reconstruction has many additional benefits compared to the internal mammary or thoracodorsal vessels. Our goal was to analyze the characteristics of these vessels and to evaluate the reliability of using them in an Asian population. Methods: Thirty-five consecutive patients were prospectively studied between November 2000 and December 2010. Twelve patients underwent muscle-sparing-2 TRAM, and 23 had DIEP flap reconstructions. Results: IMP vessels were utilized in 29 patients (83%). Most (75%) of the vessels were located in the subcutaneous plane, and 85% were in the 2nd and 3rd intercostal spaces. There were significantly more usable IMP vessels in the immediate than in the delayed reconstructions (p=0.049). All the flaps in the study were successful despite one requiring emergency reexploration due to venous congestion. Conclusions: Most of the IMP vessels are small; however, they are still reliable and safe for use as recipient vessels in selected Asian patients. The majority are located in the subcutaneous plane, which further facilitates dissection and also reduces recipient-site morbidity.